P-118 COMPLEX INCISIONAL HERNIA AFTER BRICKER PROCEDURE. A CASE REPORT. (13th October 2022) - Laguna-Hernandez, P; Serrano Yebenes, E; Diaz Pedrero, R; Soto Schutte, S; Bru Aparicio, M; Allaoua Moussaoui, Y; Mañes Jimenez, F; Jimenez Martin, R; Quiroga Valcarcel, A; Cordova Garcia, D; Alvarado Hurtado, R; Jimenez Alvarez, L; et al.
Abstract: Aim: To analyze the treatment and complications of gigant paraestomal eventration with a case report and literatura review Material and Methods: a retrospective case report from our hospital and her evolution since her urology surgery in 2011 Results: Female of 59 years old, with personal antecedents of arterial hypertension, simple cistectomy and Bricker's urinary derivation (cutaneus ureteroileostomy) in 2011 due to intersticial cistitis, parastomal incisional hernia repair with intraperitoneal mesh in 2015. The patient was derivated from urology consult for a huge paraestomal incisional hernia and personal history of obstructive uropathy and several infections of urinary tract since 2022. No obstruction clinic was associated. Elective surgery was performed with an Trasversus Abdominis Release (TAR) and moving previous urostoma: hernial sac disection and previous mesh explant. Opening Rives, Retzius spaces and transversus fasciotomy was realized. Middle line was reforzed and hernial defect was closed. Polipopilene mesh was fixed at middle line and pubis with no reabsorbible suture and reforced with haemosthatic sealant. Anterior fascia was closed fixing at middle line. At the end a new urostoma was made in ryght hypocondrium. In postoperative period the patient developed light anaemia. Following months, the patient has not other complications due to incisional hernia repair. Conclusions: Many factors can contibute to incisional hernia such as obesity, hypertension, number of surgerys, age, sex… TAR technique can be useful with complex eventration but we can not forget the commorbilities association to this surgery (anemia, pulmonar Tromboembolism…)